2015
DOI: 10.1242/jcs.161059
|View full text |Cite
|
Sign up to set email alerts
|

Rbfox proteins regulate tissue-specific alternative splicing of Mef2D required for muscle differentiation

Abstract: Among the Mef2 family of transcription factors, Mef2D is unique in that it undergoes tissue-specific splicing to generate an isoform that is essential for muscle differentiation. However, the mechanisms mediating this muscle-specific processing of Mef2D remain unknown. Using bioinformatics, we identified Rbfox proteins as putative modulators of Mef2D muscle-specific splicing. Accordingly, we found direct and specific Rbfox1 and Rbfox2 binding to Mef2D pre-mRNA in vivo. Gain-and loss-of-function experiments dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 26 publications
5
56
1
Order By: Relevance
“…We and others have shown that Mef2a and Mef2d splicing is coordinately and directly regulated by Rbfox proteins during myogenesis in culture (Runfola et al, 2015; Singh et al, 2014); we have also previously shown that the Mef2d splice variant expressed in adult skeletal muscle is required for late stages of muscle differentiation (Singh et al., 2014). Here we found that Rbfox-DKO muscle displayed significantly lower use of the β exon of Mef2a and both the α2 and β exons of Mef2d (Figures 3G, 3H, S3G, and S3H), representing a loss of muscle-specific isoforms.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…We and others have shown that Mef2a and Mef2d splicing is coordinately and directly regulated by Rbfox proteins during myogenesis in culture (Runfola et al, 2015; Singh et al, 2014); we have also previously shown that the Mef2d splice variant expressed in adult skeletal muscle is required for late stages of muscle differentiation (Singh et al., 2014). Here we found that Rbfox-DKO muscle displayed significantly lower use of the β exon of Mef2a and both the α2 and β exons of Mef2d (Figures 3G, 3H, S3G, and S3H), representing a loss of muscle-specific isoforms.…”
Section: Resultsmentioning
confidence: 69%
“…Indeed, skeletal muscle has particularly high levels of alternative splicing. We and others have shown that the splicing factors Rbfox1 and Rbfox2, which are highly conserved from C. elegans to humans (Gallagher et al, 2011; Jin et al, 2003; Kuroyanagi et al, 2007; Venables et al., 2012), are required for muscle differentiation and function (Pe-drotti et al, 2015; Runfola et al, 2015; Singh et al, 2014); but, Rbfox factors have never been studied specifically in adult skeletal muscle.…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, conditional and partial Rbfox1 depletion in satellite cells does not affect muscle regeneration, with the caveat that only ~70% knockdown was achieved (Pedrotti et al, 2015). Recent work in C2C12 cells has identified a requirement for Rbfox1 and Rbfox2 in myotube differentiation in vitro (Runfola et al, 2015). Future studies in satellite cells in vivo and during regeneration may shed light on potential roles for Rbfox RNA-binding proteins in satellite cell regulation and skeletal muscle regeneration in vertebrates.…”
Section: Discussionmentioning
confidence: 99%
“…For example, MEF2D α1 and α2 MXEs were misspliced (Fig. 1B), an event linked to impaired myogenesis (Singh et al 2014;Runfola et al 2015), and misregulation of this and additional targets was confirmed by RT-PCR (Fig. 1C).…”
Section: Severe Rna Misprocessing In Cdmmentioning
confidence: 90%